MATHNECT: Mathematics Motion Based Learning for Primary School - Rejmi, Zaki Hakimi; Mohamad Rasli, Roznim (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Courseware is now widely used in the process of learning and teaching, particularly at the primary school level and in mathematics classes. Students become less interested in learning mathematics because it involves abstract and complex concepts. Difficulty learning math is a profound and acknowledged difficulty among students throughout the generations. The way of teaching and learning mathematics has remained relatively the same in our education system. Students are unable to provide their entire focus in class because of the current educational system, which is sometimes boring and relies solely on the whiteboard as a medium of instruction. However, with today's technological advancements, this problem may be overcome. It can be used to enhance the current educational system by utilizing current technology. One of them is Kinect, this device is a motion-tracking technology that allows users to interact with applications by moving their bodies. The main objective of this Mathnect is to develop a motion-based learning environment by utilizing Kinect technology as a learning aid to improve student concentration and attention in mathematics class. This project is developed using a methodology ADDIE. The methodology of analysis employed in this phase, which includes content analysis, should be focused on the compatibility of the content and the target users. The game will be focusing on teaching simple mathematics number, which it will cover on basic numbers among primary school students. Thus, by implementing this project in primary schools, our educational environment can be improved to produce new adaptive learning methods. This Mathnect is beneficial for educators, students, and parents to be used in the classroom and can also be used for self-based learning. As a result, students will not be bored in the classroom at any time.